Mutational Patterns in Pancreatic Juice of Intraductal Papillary Mucinous Neoplasms and Concomitant Pancreatic Cancer. Issue 8 (September 2019) - Takano, Shinichi; Fukasawa, Mitsuharu; Kadokura, Makoto; Shindo, Hiroko; Takahashi, Ei; Hirose, Sumio; Fukasawa, Yoshimitsu; Kawakami, Satoshi; Hayakawa, Hiroshi; Maekawa, Shinya; Mochizuki, Kunio; Kawaida, Hiromichi; et al.
Abstract : Objectives: The aims of this study were to identify genetic characteristics of intraductal papillary mucinous neoplasm (IPMN)-associated pancreatic ductal carcinoma (PDC) and to detect these markers using pancreatic juice. Methods: From 76 cases, 102 tissues were obtained: 29 cases were noninvasive IPMN, 18 were PDC derived from IPMN (D-PDC; noninvasive part, n = 16; invasive part, n = 18), and 29 were PDC concomitant with IPMN (C-PDC; IPMN part, n = 10; PDC part, n = 29). Moreover, pancreatic juice samples from 28 cases were obtained (noninvasive IPMN, n = 13; D-PDC, n = 7; C-PDC, n = 8). Fifty-one cancer-related genes were analyzed by next-generation sequencing. Results: TP53 mutation rates in D-PDC, C-PDC, and noninvasive IPMN were 67%, 66%, and 10%, respectively. Moreover, KRAS mutational patterns between 2 simultaneous tumors differed in 1 (6.3%) of the 16 D-PDC cases and in 8 (80%) of the 10 C-PDC cases ( P = 0.0006). TP53 or multiple KRAS mutations were detected using pancreatic juice more frequently in C-PDC cases than in noninvasive IPMN cases (75% and 23%, respectively, P = 0.03). Conclusions: Multiple KRAS mutations along with TP53 mutation are genetic markers for C-PDC, which could be detected using pancreatic juice preoperatively. Abstract : Supplemental digital content is available in the text.